Emerging Molecular and Atomic Level Techniques for Nanoscale Applications. (January 2018) - Kaloyeros, Alain E.; Goff, Jonathan; Arkles, Barry
Abstract : This overview provides an introduction and comparison of emerging processing technologies that represent the best contenders to satisfy future demands for ultrathin film applications. In particular, ALD, MLD, SAM, and CCD are newer techniques for ultrathin or near-zero-thickness film fabrication. These techniques are now entering early stages of commercialization, especially in biosensors, semiconductors and hetero-devices. This article introduces these techniques with emphasis on process descriptions and definitions in order to provide clarification and is illustrated with application examples. Sufficient citations are provided to allow the interested reader to pursue the subjects in more depth, but are not intended to be comprehensive.